High-temperature-resistant coal catalytic gasification catalyst and preparation method thereof

By pyrolysis of coal base, impregnation of organometallic salt, modification of ammonium salt and ion exchange processes, the problems of existing catalysts inactivation and poor dispersion at high temperatures are solved, and the efficiency of coal catalytic gasification is achieved. Improvement and stability improvement.

CN119114069AActive Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202310683472.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-13
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

The existing coal catalytic gasification catalysts are prone to deactivate at high temperatures, and the accumulation of alkali metal catalysts on the coal surface and slag formation leads to a reduction in the catalytic gasification efficiency, making it difficult to achieve uniform dispersion and efficient catalysis.

Method used

Semicoke was prepared by pyrolyzing the coal base, and the alkali metal organometallic salt was impregnated, followed by modification treatment with ammonium salt, and finally, the active components were compounded through the ion exchange process to prepare a high-temperature-resistant composite Catalyst, improves the uniformity and activity of the catalyst.

Benefits of technology

The distribution uniformity and utilization of active components of the catalyst are significantly improved, the formation of insoluble potassium aluminum silicate is reduced, the fluidity and diffusion capacity of the catalyst are enhanced, and the efficiency and stability of coal catalytic gasification are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114069A_ABST
    Figure CN119114069A_ABST
Patent Text Reader

Abstract

The invention provides a high-temperature-resistant coal catalytic gasification catalyst and a preparation method thereof, and relates to the field of catalysts. The method comprises the following steps: carrying out pyrolysis treatment on a coal base to obtain semi-coke, dipping the semi-coke in organic metal salt of alkali metal to form a catalyst precursor, adding a modifier into the catalyst precursor for modification treatment, and compounding the modified catalyst precursor with an active component in an ion exchange mode to prepare the composite catalyst. When the prepared catalyst reacts for 300 minutes, the conversion rate reaches 89.1%, the accumulated methane generation amount reaches 12.9 mmol.g <-1 >, the content of methane in the product reaches 26.4%, and the catalyst shows excellent methane preparation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a high-temperature resistant coal catalytic gasification catalyst and a preparation method thereof. Background Art

[0002] Coal catalytic gasification technology was first developed in 1976, during which time Exxon and GreatPoint Energy both proposed coal catalytic gasification solutions. In China, after years of exploration, ENN has successfully developed a complete coal catalytic gasification process system, with technology reaching the international leading level, and has started industrial production since 2017.

[0003] The prior art has reported a large number of schemes for using sodium carbonate as a catalyst to achieve coal catalytic gasification. Potassium and sodium carbonates, alkaline earth metals and transition metal salts are all good catalysts for coal catalytic gasification. Coal catalytic gasification is a typical gas-solid heterogeneous reaction. The gas phase reactants must react with carbon on the surface of the coal carrying the catalyst. The activity of the catalyst depends on the specific surface area of ​​the coal and its dispersion on the coal surface. Sodium carbonate / potassium on the coal surface, in addition to removing the active centers of the surface oxide groups formed by alkali metals and carbon, will also change the pore structure of the coal surface, and further melting and diffusion at the gasification temperature can improve the activity of the coal. For example, ExxonMobil Corporation of the United States has developed a coal pressurized fluidized bed catalytic gasification process for the purpose of producing substitute natural gas using K2CO3 as a catalyst. After adding K2CO3 catalyst, the carbon conversion rate is greatly improved within the same reaction time, and the reaction rate is increased by about 4 times.

[0004] Compared with single-component catalysts, researchers have paid extensive attention to multi-component catalysts with higher gasification efficiency in recent years. For example, a mixture of K2SO4 and FeSO4 was used as a catalyst to study the gasification of Pittsburgh HVA coal char. The reaction conditions were: K / Fe molar ratio of 9, temperature of 850°C, pressure of 0.1MPa, metal / carbon atomic ratio of 0.02, metal loading of 5.1-7.3g / 100g carbon, carbon particle size of 53μm-106μm, reaction gas of H2O / H2 or H2O / N2 (H2O content of 30%), and the carbon conversion rate could reach 100%; under the same reaction conditions, using K2CO3 alone as a catalyst, the carbon conversion rate was only 89%. For example, the kinetics of coal gasification were studied using the three-way catalyst Li2CO3-Na2CO3-K2CO3, the binary catalyst Na2CO3-K2CO3, and the monomer catalyst K2CO3. It was found that the activation energy of catalytic gasification by the three-way catalyst was lower than that by the binary catalyst and the monomer catalyst. This is because at the gasification temperature of 700-900°C, the three-way catalyst is in liquid state, while the binary catalyst and the monomer catalyst K2CO3 are in solid state. The liquid catalyst has good fluidity and is easier to diffuse into the reaction system. The active sites of the coal increase accordingly, so the activity is relatively high. The study also found that the accumulation or excess of sodium carbonate / potassium as a catalyst on the surface of coal is easy to stick to each other and slag in the molten state, which has an adverse effect on the catalytic gasification process.

[0005] Therefore, it is urgent to develop an alkali metal catalyst that is not easily deactivated, resistant to high temperatures, has good coal catalytic gasification effect, and is easier to disperse evenly, so as to break through the bottleneck of the industrialization of coal catalytic gasification technology. Summary of the invention

[0006] The purpose of the present invention is to provide a high temperature resistant coal catalytic gasification catalyst and a preparation method thereof. The preparation process of the catalyst precursor greatly improves the uniformity, dispersibility and porosity of the coal base in the catalyst, and when the active components are compounded, the utilization rate of the active components can be significantly improved, thereby enhancing the activity of the catalyst.

[0007] To achieve the above object, the present invention proposes the following technical solutions:

[0008] In a first aspect, the present invention discloses a method for preparing a high temperature resistant coal catalytic gasification catalyst, comprising the following steps:

[0009] 1) Pyrolysis of coal to obtain semi-coke;

[0010] 2) impregnating the semi-coke with an organic metal salt of an alkali metal to obtain a catalyst precursor;

[0011] 3) Modifying the catalyst precursor;

[0012] 4) The modified catalyst precursor is composited with active components by an ion exchange process, and the product is post-treated to obtain a high temperature resistant composite catalyst.

[0013] Furthermore, based on the mass percentage of the oxides and the total amount of the oxides being 100%, the semi-coke obtained in step 1) comprises: Fe2O3 8.85%, Al2O3 19.87%, SiO2 32.33%, K2O18.69%, Cr2O31.55%, CaO 12.98%, NiO 0.82%, MgO 2.96%, Na2O 1.74%, and MnO0.21%.

[0014] Furthermore, the reaction conditions for preparing semi-coke by pyrolysis of coal-based in step 1) are:

[0015] In a fluidized bed reactor, in a N2 / H2 atmosphere at a temperature of 450-850°C, the coal base is heated until the pyrolysis reaction is completed; wherein the coal base is one or more of bituminous coal, lignite, peat, petroleum coke or anthracite.

[0016] Wherein, the coal base is one or more of bituminous coal, lignite, peat, petroleum coke or anthracite.

[0017] Furthermore, the semi-coke has a particle size of 0.6 to 1 cm and a porosity of 30 to 50%.

[0018] Furthermore, the conditions for the impregnation treatment of the semi-coke with an organic metal salt of an alkali metal in step 2) are as follows: under a N2 atmosphere, the semi-coke is immersed in a reaction vessel containing an organic metal salt solution of the alkali metal, and stirred for 2 to 5 hours at a temperature of 40 to 75°C to obtain a catalyst precursor; wherein the organic metal salt of the alkali metal is selected from one or any combination of sodium dodecylbenzene sulfonate, sodium oleate, potassium dodecylbenzene sulfonate, potassium oleate and potassium salt of polyacrylamide.

[0019] Furthermore, in step 3), the catalyst precursor is modified by using ammonium salt as a modifier, and the pH of the mixed solution in the reaction container is controlled to be greater than 7.5 during the modification process.

[0020] Furthermore, the ammonium salt is selected from one or more of (NH4)2CO3, NH4HCO3, NH4NO3, (NH4)2SO4, and NH4Cl.

[0021] Furthermore, the active components in step 4) are selected from at least two of sodium salt, magnesium salt, potassium salt, calcium salt, manganese salt, iron salt, cobalt salt and nickel salt.

[0022] Furthermore, the reaction conditions of the ion exchange process are: the ion exchange reaction temperature is 20-200° C., the pressure is 0.1-1.6 MPa, and the reaction time is 10-60 min.

[0023] In a second aspect, the present invention discloses a high temperature resistant coal catalytic gasification catalyst, which is prepared by the above-mentioned preparation method of the high temperature resistant coal catalytic gasification catalyst; wherein the coal catalytic gasification catalyst comprises, by weight, 80-93% of a catalyst precursor, 2-5% of a modifier, and 5-15% of an active component.

[0024] It can be seen from the above technical solutions that the present invention has the following beneficial effects:

[0025] The high temperature resistant coal catalytic gasification catalyst and its preparation method disclosed in the present invention first prepare semi-coke and impregnate it with organic metal salt to form a catalyst precursor, then use ammonium salt to modify the catalyst precursor to form a composite active component, and finally obtain a high temperature resistant composite catalyst, whose active component distribution is more uniform and has excellent coal catalytic gasification effect. The advantages include the following:

[0026] 1. The coal base is pyrolyzed to obtain semi-coke, which is then immersed in an organic metal salt of an alkali metal to form a catalyst precursor, thereby improving the uniformity, dispersion and porosity of the coal base.

[0027] 2. During the catalyst preparation process, ammonium salt is used to modify the catalyst precursor. By controlling the pH, the prepared composite catalyst is made weakly alkaline, which reduces the formation of insoluble potassium aluminum silicate during coal catalytic gasification and improves the utilization rate of active components.

[0028] 3. The active components in the composite catalyst have a lower melting point and can melt at a lower temperature and then penetrate into the pores of the coal-based material during the reaction, making the distribution of the active components more uniform. At the same time, it has good fluidity and is easier to diffuse into the reaction system, and the active sites of the coal increase accordingly.

[0029] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.

[0030] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are not drawn to scale according to actual reference objects. In the accompanying drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For the sake of clarity, not every component is labeled in each figure. Now, embodiments of various aspects of the present invention will be described by way of example and with reference to the accompanying drawings, in which:

[0032] Figure 1 This is a flow chart for preparing the coal catalytic gasification catalyst of the present invention;

[0033] Figure 2 This is a TEM image of the catalyst prepared in Comparative Example 1 of the present invention;

[0034] Figure 3 This is the TEM image of the catalyst prepared in Example 12 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meaning understood by people with general skills in the field to which the present invention belongs.

[0036] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0037] Based on the research, it is found that when alkali metal salts are used as catalysts in the coal catalytic gasification process, although good catalytic effects are achieved in the early stage, as the catalyst is used for a long time, the accumulation of molten sodium carbonate / potassium on the coal surface leads to mutual adhesion and slagging deactivation, thereby affecting the coal catalytic gasification effect and significantly reducing the catalytic efficiency. The present invention aims to address this problem and propose a high temperature resistant coal catalytic gasification catalyst and a preparation method thereof, which is not only resistant to high temperatures, has excellent catalytic effects, but is also not easy to deactivate.

[0038] Specific as Figure 1 As shown, the preparation method of the high temperature resistant coal catalytic gasification catalyst disclosed in the present invention comprises the following steps:

[0039] 1) pyrolyzing a coal-based material to obtain semi-coke; wherein the reaction conditions for obtaining the semi-coke by pyrolyzing the coal-based material are as follows: in a fluidized bed reactor, the coal-based material is heated to 450-850° C. in a N2 / H2 atmosphere until the pyrolysis reaction is completed; the coal-based material is one or more of bituminous coal, lignite, peat, petroleum coke or anthracite; the semi-coke obtained comprises, in terms of mass percentage based on oxides and the total amount of the oxides being 100%, Fe2O3 8.85%, Al2O3 19.87%, SiO2 32.33%, K2O18.69%, Cr2O3 1.55%, CaO 12.98%, NiO 0.82%, MgO 2.96%, Na2O 1.74%, MnO 0.21%, and the particle size of the semi-coke is 0.6-1 cm and the porosity is 30-50%;

[0040] 2) The semi-coke is impregnated with an organic metal salt of an alkali metal to obtain a catalyst precursor; wherein the conditions for the impregnation treatment are: under a N2 atmosphere, the semi-coke is impregnated in a reaction vessel containing an organic metal salt solution of the alkali metal, and stirred at a temperature of 40 to 75°C for 2 to 5 hours to obtain a catalyst precursor; wherein the organic metal salt of the alkali metal is selected from one or any combination of sodium dodecylbenzene sulfonate, sodium oleate, potassium dodecylbenzene sulfonate, potassium oleate and potassium salt of polyacrylamide;

[0041] 3) using ammonium salt as a modifier to modify the catalyst precursor, and during the modification process, the pH of the mixed solution in the reaction container is controlled to be greater than 7.5; the ammonium salt is selected from one or more of (NH4)2CO3, NH4HCO3, NH4NO3, (NH4)2SO4, and NH4Cl;

[0042] 4) The modified catalyst precursor is composited with active components by an ion exchange process, and the product is post-processed to obtain a high temperature resistant composite catalyst; wherein the coal catalytic gasification catalyst comprises, by weight, 80-93% of catalyst precursor, 2-5% of modifier, and 5-15% of active components; the reaction conditions of the ion exchange process are: the ion exchange reaction temperature is 20-200°C, the pressure is 0.1-1.6MPa, and the reaction time is 10-60min; the active components are selected from at least two of sodium salt, magnesium salt, potassium salt, calcium salt, manganese salt, iron salt, cobalt salt, and nickel salt.

[0043] The high temperature resistant coal catalytic gasification catalyst and the preparation method thereof disclosed in the present invention will be further specifically introduced below in conjunction with the specific embodiments shown in the accompanying drawings.

[0044] Example 1

[0045] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke; place the semi-coke in a reactor and immerse it in 0.25mol / L sodium oleate under N2 atmosphere with a stirring time of 5h at a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with Na2CO3 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 200℃, the pressure is 0.1MPa, and the reaction time is 60min; after the reaction, the product is post-treated, including washing, centrifugation, drying, and grinding, and the prepared catalyst is marked as S-1.

[0046] Example 2

[0047] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 600℃ under N2 / H2 atmosphere, and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L sodium oleate under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with MgCO3 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 200℃, the pressure is 0.1MPa, and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-2.

[0048] Example 3

[0049] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 450℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L sodium oleate under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with CoCO3 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 200℃, the pressure is 0.1MPa, and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-3.

[0050] Example 4

[0051] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 850℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L sodium dodecylbenzene sulfonate under N2 atmosphere, with a stirring time of 2h and a temperature of 75℃; add (NH4)2CO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 9; after the prepared precursor is modified, ion exchange is carried out with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 20℃, the pressure is 0.1MPa, and the reaction time is 10min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-4.

[0052] Example 5

[0053] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere, and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke. The obtained semi-coke is placed in a reactor, and in N2 atmosphere, the semi-coke is immersed in 0.25mol / L potassium dodecylbenzene sulfonate, with a stirring time of 5h and a temperature of 75℃; (NH4)2CO3 is added dropwise to the obtained catalyst precursor for modification treatment until the pH of the mixed solution is 9, and after the prepared precursor is modified, ion exchange is performed with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 20℃, the pressure is 0.1MPa, and the reaction time is 10min; after the reaction, the product is post-treated, and the obtained catalyst is marked as S-5.

[0054] Example 6

[0055] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 850℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L polyacrylamide potassium salt under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add (NH4)2CO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 9; after the prepared precursor is modified, ion exchange is carried out with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 20℃, the pressure is 0.1MPa, and the reaction time is 10min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-6.

[0056] Example 7

[0057] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 850℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L sodium oleate under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add NH4NO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 9; after the prepared precursor is modified, ion exchange is carried out with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 100℃, the pressure is 0.2MPa, and the reaction time is 30min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-7.

[0058] Example 8

[0059] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere, and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke. The obtained semi-coke is placed in a reactor, and in N2 atmosphere, the semi-coke is immersed in 0.25mol / L sodium oleate, with a stirring time of 5h and a temperature of 75℃; (NH4)2SO4 is added dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 9; after the prepared precursor is modified, ion exchange is carried out with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 100℃, the pressure is 0.2MPa, and the reaction time is 60min; the product is post-treated after the reaction; the product is post-treated after the reaction, and the obtained catalyst is marked as S-8.

[0060] Example 9

[0061] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 850℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L sodium oleate under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with Ni(NO3)2 and K2CO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 150℃, the pressure is 0.2MPa, and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-9.

[0062] Example 10

[0063] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor, heat the coal to 850℃ under N2 / H2 atmosphere, maintain the temperature until the coal-based pyrolysis reaction is completed, and obtain semi-coke; place the obtained semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L potassium oleate under N2 atmosphere, with a stirring time of 5h and a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification treatment until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with K2CO3 and CoCO3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 150℃, the pressure is 0.2MPa, and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-10.

[0064] Embodiment 11

[0065] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke; place the prepared semi-coke in a reactor, and immerse the semi-coke in 0.25mol / L potassium oleate under N2 atmosphere with a stirring time of 5h at a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with K2CO3 and Fe(NO3)3 with a concentration of 0.25mol / L, the ion exchange reaction temperature is 150℃, the pressure is 0.2MPa, and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-11.

[0066] Example 12

[0067] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke; place the obtained semi-coke in a reactor and immerse the semi-coke in 0.25mol / L potassium oleate under N2 atmosphere with a stirring time of 5h at a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with K2CO3, Mn(NO3)2 and Ni(NO3)2 at a concentration of 0.25mol / L, the ion exchange reaction temperature is 150℃, the pressure is 0.2MPa and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-12.

[0068] Comparative Example 1

[0069] Take 50g of 60-100 mesh anthracite and place it in a fluidized bed reactor. Heat the coal to 850℃ under N2 / H2 atmosphere and maintain the temperature until the coal-based pyrolysis reaction is completed to obtain semi-coke; place the obtained semi-coke in a reactor and immerse the semi-coke in 0.25mol / L potassium carbonate under N2 atmosphere with a stirring time of 5h and a temperature of 75℃; add NH4HCO3 dropwise to the prepared catalyst precursor for modification until the pH of the mixed solution is 8; after the prepared precursor is modified, ion exchange is carried out with K2CO3, Mn(NO3)2 and Ni(NO3)2 at a concentration of 0.25mol / L, the ion exchange reaction temperature is 150℃, the pressure is 0.2MPa and the reaction time is 60min; after the reaction, the product is post-treated and the prepared catalyst is marked as S-13.

[0070] Catalyst performance evaluation

[0071] Evaluation conditions: gasification temperature 700℃, gasification pressure 3.5Mpa, initial water-coal ratio 2g / g·min -1 , carrier gas (Ar gas) flow rate 1L / min. The fixed bed reactor has an inner diameter of 32mm and a height of 800mm. The product gas enters the separation tank for gas-liquid separation. The separated gas is dehumidified by a dryer, measured by a wet flow meter, and then collected by a gas bag. Finally, the product gas composition and content in each period of time are analyzed by GC. Specific analysis data are shown in Table 1.

[0072] Table 1 Coal gasification conversion rate, methane production and methane content at reaction time 300 min

[0073]

[0074] It can be seen from the catalytic data in Table 1 that in the coal catalytic gasification reaction, under the same experimental conditions, the S-12 catalyst prepared according to the method of the present invention has the highest conversion rate of coal gasification into gas phase products. When the reaction time is 300 min, the conversion rate reaches 89.1%, and the cumulative methane production reaches 12.9 mmol·g -1 The methane content in the product reached 26.4%, showing excellent methane production performance.

[0075] In this regard, catalysts S-12, S-13 and raw coal were analyzed from the perspective of microstructure to explain the reasons for the excellent catalytic performance of S-12.

[0076] Table 2 Catalyst BET full analysis data

[0077] catalyst Pore ​​volume ml / g Average pore size nm <![CDATA[Specific surface area m 2 / g]]> S-13 0.0050 8.411 1.188 S-12 0.0059 6.498 2.146 raw coal 0.0081 6.667 2.434

[0078] Combined with the BET pore size analysis data, it shows that compared with the raw coal, catalysts S-12 and S-13 have changed the pore structure of the raw coal to varying degrees, and the pore volume and specific surface area have decreased; among them, catalyst S-12 has a larger pore volume and a smaller average pore size, but still has a rich pore structure and a large specific surface area. However, further research on the distribution of active components in the catalyst found that only a few potassium carbonate molecules in catalyst S-13 entered the pores on the surface of the semi-coke, and most of them existed on the surface of the coal powder, and the dispersion was poor, with obvious accumulation, such as Figure 2 shown; Figure 3 In the microscopic image of catalyst S-12 shown, it can be clearly seen that potassium oleate molecules are evenly dispersed in the coal powder, and no accumulation phenomenon can be seen; the reason is that the anion of potassium oleate with lipophilic groups improves the binding ability of alkali metal ions with the coal surface, so that potassium ions are fully and evenly dispersed on the surface of the coal. In summary, catalyst S-12 has a rich pore structure and a large specific surface area. After the modified catalyst, the active components are fully and evenly dispersed on the surface of the coal agent, thereby showing excellent methanation performance.

[0079] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a high temperature resistant coal catalytic gasification catalyst, characterized in that: The steps include: 1) Pyrolysis of coal to obtain semi-coke; 2) impregnating the semi-coke with an organic metal salt of an alkali metal to obtain a catalyst precursor; 3) Modifying the catalyst precursor; 4) The modified catalyst precursor is composited with active components by an ion exchange process, and the product is post-treated to obtain a high temperature resistant composite catalyst.

2. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 1, characterized in that: Calculated by mass percentage based on oxides and with the total amount of the oxides being 100%, the semi-coke prepared in step 1) comprises: Fe2O3 8.85%, Al2O3 19.87%, SiO2 32.33%, K2O 18.69%, Cr2O3 1.55%, CaO 12.98%, NiO0.82%, MgO 2.96%, Na2O 1.74%, and MnO 0.21%.

3. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 1, characterized in that: The reaction conditions for preparing semi-coke by pyrolysis of coal in step 1) are: In a fluidized bed reactor, in a N2 / H2 atmosphere at a temperature of 450-850°C, the coal base is heated until the pyrolysis reaction is completed; wherein the coal base is one or more of bituminous coal, lignite, peat, petroleum coke or anthracite.

4. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 1, characterized in that: The particle size of the semi-coke is 0.6-1 cm, and the porosity is 30-50%.

5. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 1, characterized in that: The conditions for the step 2) of using an organic metal salt of an alkali metal to impregnate the semi-coke are: Under N2 atmosphere, the semi-coke is immersed in a reaction vessel containing an organic metal salt solution of the alkali metal, and stirred for 2 to 5 hours at a temperature of 40 to 75°C to obtain a catalyst precursor; wherein the organic metal salt of the alkali metal is selected from one or any combination of sodium dodecylbenzene sulfonate, sodium oleate, potassium dodecylbenzene sulfonate, potassium oleate and potassium polyacrylamide.

6. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 5, characterized in that: In the step 3), the catalyst precursor is modified by using ammonium salt as a modifier, and the pH of the mixed solution in the reaction container is controlled to be greater than 7.5 during the modification process.

7. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 6, characterized in that: The ammonium salt is selected from one or more of (NH4)2CO3, NH4HCO3, NH4NO3, (NH4)2SO4, and NH4Cl.

8. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 1, characterized in that: The active components of step 4) are selected from at least two of sodium salt, magnesium salt, potassium salt, calcium salt, manganese salt, iron salt, cobalt salt and nickel salt.

9. The method for preparing the high temperature resistant coal catalytic gasification catalyst according to claim 8, characterized in that: The reaction conditions of the ion exchange process are: the ion exchange reaction temperature is 20-200° C., the pressure is 0.1-1.6 MPa, and the reaction time is 10-60 min.

10. A high temperature resistant coal catalytic gasification catalyst, characterized in that: The high temperature resistant coal catalytic gasification catalyst is prepared by the preparation method of any one of claims 1 to 9; wherein the coal catalytic gasification catalyst comprises, by weight, 80-93% of catalyst precursor, 2-5% of modifier, and 5-15% of active component.

Citation Information

Patent Citations

  • Catalytic coal gasification catalyst and preparation method and application thereof

    CN104437563A

  • Catalysts based on natural minerals and process for gasification using the same

    CN105312056A

  • Lignite catalytic gasification raw material and preparation method thereof

    CN109423338A

Cited By

  • Catalyst for regulating and controlling catalytic pyrolysis product of oil-rich coal as well as preparation method and application of catalyst

    CN119857523A